Novel pyrazolo[1, 5-a]pyridines with improved aqueous solubility as p110α-selective PI3 kinase inhibitors. Issue 2 (15th January 2017) - Kendall, Jackie D.; Giddens, Anna C.; Tsang, Kit Yee; Marshall, Elaine S.; Lill, Claire L.; Lee, Woo-Jeong; Kolekar, Sharada; Chao, Mindy; Malik, Alisha; Yu, Shuqiao; Chaussade, Claire; Buchanan, Christina; et al.
Graphical abstract: Abstract: As part of our investigation into pyrazolo[1, 5- a ]pyridines as novel p110α selective PI3 kinase inhibitors, we report a range of analogues with improved aqueous solubility by the addition of a basic amine. The compounds demonstrated comparable p110α potency and selectivity to earlier compounds but with up to 1000× greater aqueous solubility, as the hydrochloride salts. The compounds also displayed good activity in a cellular assay of PI3 kinase activity.